Assessment of glutamine and glutamic acid in guinea pig (Cavia porcellus) diets on the structure and intestinal enzymatic activity, and the productive and economic performance - Castillo Soto, W. (2022)
The effect of glutamine and glutamic acid added to the diet of guinea pigs (Cavia porcellus) on the intestinal structure and the activity of digestive enzymes, as well as on the productive and economic response, was determined. In total, 100 guinea pigs of both sexes, 15 days old, with an initial weight of 358.8 + 27.5 g were used in two phases (Initial from 15 to 32 days and Growth from 33 to 74 days of age). Four levels of the commercial product AminoGut® (0, 0.025, 0.050 and 0.075%) were included in the diet through a complete randomized design with four repetitions. A better body weight gain and feed conversion rate were observed in the initial phase through a quadratic trend (p<0.05), with a better response at the level of 0.056% of inclusion; however, there was no significant effect on the growth phase or the global one. In the intestinal structure, on day 5 of weaning, deeper crypts with higher inclusion levels were observed, but without affecting the villi/crypt ratio. Likewise, the activity of the maltase enzyme showed a quadratic trend (p<0.05) with higher activity at the estimated level of 0.048% of AminoGut® in the diet, although there was no effect on day 8 post-weaning. The economic benefit and profitability were greater in the treatments that received higher levels of inclusion. It is concluded that the supplementation of glutamine and glutamic acid was satisfactory for the productive and economic performance of the guinea pigs, giving better responses with the higher levels used in the diet.